2021
DOI: 10.1093/pm/pnab179
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Neighborhood Deprivation and Perceived Changes for Pain-Related Experiences Among US Patients with Chronic Low Back Pain During the COVID-19 Pandemic

Abstract: Objective Disruptions caused by the COVID-19 pandemic could disproportionately affect the health of vulnerable populations, including patients experiencing persistent health conditions (i.e., chronic pain), along with populations living within deprived, lower socioeconomic areas. The current cross-sectional study characterized relationships between neighborhood deprivation and perceived changes in pain-related experiences during the COVID-19 pandemic (early-September to mid-October 2020) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These questions have been used previously to understand the impact of the COVID-19 pandemic on patients managing chronic low back pain. [14] …”
Section: Methodsmentioning
confidence: 99%
“…These questions have been used previously to understand the impact of the COVID-19 pandemic on patients managing chronic low back pain. [14] …”
Section: Methodsmentioning
confidence: 99%
“…The pandemic decreased psychological support and reduced ability of chronic pain patients to employ coping strategies for pain [90][91][92]. Even in studies that showed no increase in pain, other measures of quality of life such as coping, mood and social support worsened during the lockdown [93][94][95]. Scores of physical and mental well-being seemed to universally decrease in all countries due to the pandemic [63], and introverted patients [96] or those with increased social isolation or loneliness [23] were more likely to experience increased pain.…”
Section: Pandemic Influence On Patients With Pre-existing Chronic Painmentioning
confidence: 99%
“… 10 , 54 , 102 This is a necessary conceptual shift for pain researchers because, to date, the focus has almost exclusively been on characterizing racialized disparities and examining the role of the individual, with some investigators occasionally assessing interpersonal cognitive–behavioral contributors to disparate pain outcomes. 32 , 76 , 82 , 88 Second, research has almost always centered responsibility for racialized pain disparities on minoritized individuals (eg, their perceptions and behaviors). 8 , 98 Conversely, a broader justice orientation shifts the focus away from the individual by contextualizing the multiple levels of injustice that can be targeted for intervention.…”
Section: Relevance Of Injustice To Healthmentioning
confidence: 99%